Cellular and Molecular Connections between Autophagy and Inflammation - Pierre Lapaquette; Jean Guzzo; Lionel Bretillon; Marie-Agnès Bringer (Mediators of Inflammation)
Autophagy is an intracellular catabolic pathway essential for the recycling of proteins and larger substrates such as aggregates, apoptotic corpses, or long-lived and superfluous organelles whose accumulation could be toxic for cells. Because of its unique feature to engulf part of cytoplasm in double-membrane cup-shaped structures, which further fuses with lysosomes, autophagy is also involved in the elimination of host cell invaders and takes an active part of the innate and adaptive immune response. Its pivotal role in maintenance of the inflammatory balance makes dysfunctions of the autophagy process having important pathological consequences. Indeed, defects in autophagy are associated with a wide range of human diseases including metabolic disorders (diabetes and obesity), inflammatory bowel disease (IBD), and cancer. In this review, we will focus on interrelations that exist between inflammation and autophagy. We will discuss in particular how mediators of inflammation can regulate autophagy activity and, conversely, how autophagy shapes the inflammatory response. Impact of genetic polymorphisms in autophagy-related gene on inflammatory bowel disease will be also discussed.